The Bhagavad-gita : Krishna's counsel in time of war - Miller, Barbara Stoler (New York, NY, USA : Bantam Books, 1986)
Recounts the tale of Arjuna, a warrior-prince who is forced to confront a life-or-death moral dilemma as he tries to determine the purpose of war.
Keywords: Hindi literature; Hinduism -- Sacred books